Prognostic role of intraparotid lymph node metastasis in primary parotid cancer: Systematic review - Guntinas-Lichius, Orlando; Thielker, Jovanna; Robbins, K. Thomas; Olsen, Kerry D.; Shaha, Ashok R.; Makitie, Antti A.; Bree, Remco de; Vander Poorten, Vincent; Quer, Miquel; Rinaldo, Alessandra; Kowalski, Luiz Paulo [UNESP]; Rodrigo, Juan Pablo; et al. (Wiley-Blackwell, 2020)
Background The prognostic importance of intraparotid lymph node metastasis (P+) in patients with primary parotid gland carcinoma is unclear. Methods Nineteen retrospective and noncomparative cohort studies, published between 1992 and 2020, met the inclusion criteria and included 2202 patients for this systematic review. Results The pooled prevalence of the P in adult patients in the unselected studies was 24.10% (95% confidence interval = 17.95-30.25). The number of P+ lymph nodes per patient was counted in only three studies and ranged from 1 to 11. The 5-year recurrence-free survival rate based on Kaplan-Meier analysis varied from 83% to 88% in P- patients compared to 36% to 54% in P+ patients. The average hazard ratio for tumor recurrence in patients with P+ compared to P- was 2.67 +/- 0.58. Conclusions P+ is an independent negative prognostic factor in primary parotid gland cancer and should be included into the treatment planning.
Keywords: clinical significance; intraparotid lymph node metastasis; nodal metastasis; prevalence; primary parotid cancer; survival